Health Benefits of Electrifying Chicago's Municipal Vehicle Fleet - Anastasia Montgomery, MS; Jordan L Schnell, PhD; Amy Rogin, BS; Daniel E Horton, ProfPhD (The Lancet Planetary Health, 2021)
Background: Approximately 100 000 American citizens die prematurely each year from air pollution exposure. To lower ambient pollution and co-emitted greenhouse gases, some cities have enacted vehicle electrification policies. In this study, we aimed to simulate changes in atmospheric composition due to the electrification of Chicago's municipal vehicle fleet and quantify the corresponding health and climate benefits of this policy. Methods: We simulated air quality at the neighbourhood scale (1·3 × 1·3 km) over the Chicago metropolitan area using the coupled Weather Research Forecast and Community Multiscale Air Quality Modelling System chemistry-climate model. We modified the 2014–16 National Emissions Inventory to create input emissions for baseline and electric vehicle adoption scenarios in Summer (August 2018) and Winter (January 2019) months. In the electric vehicle adoption scenario, we removed combustion products of the municipal vehicle fleet (school buses, transit buses, and refuse trucks) from the emissions data. To quantify the health effects of electric vehicle adoption, we calculated the difference in health response between the baseline and electrification scenarios by use of a suite of health response functions. Findings: We found that fleet electrification reduced CO2 emissions (–1·4%) and NO2 concentrations (–1·0%) while modestly increasing O3 concentrations (+0·3%). Monthly average NO2 reductions were found in high-density areas and along interstate highways, whereas O3 increases were more prominent in the Chicagoland suburbs. Particulate matter changes were modest and spatially heterogenous. The pollutant changes resulted in both positive and negative health outcomes that were largely off setting. Interpretation: The inverse relationship between O3 and NO2 is known as the “weekend effect”, in which the removal of NO2 results in an increase in O3 due to titration in volatile organic compound-limited environments. This relationship is particularly evident over the highways, where excess NO2 reduces O3 concentrations. The decision to electrify vehicles should consider air quality changes in addition to CO2 due to complicating chemical interactions within urban environments. Funding: Ubben Program for Carbon and Climate Science at Northwestern University, US National Science Foundation.